A new strategy to improve viscoelasticity, crystallization and mechanical properties of polylactide. (May 2021) - Huang, Ying; Müller, Michael Thomas; Boldt, Regine; Zschech, Carsten; Gohs, Uwe; Wießner, Sven
Abstract: Biodegradable polylactide/masticated natural rubber (PLA/mNR) blends were prepared by electron induced reactive processing (EIReP) without using any chemical additives. The PLA/mNR blends showed droplet-matrix morphology with decreased mNR particle size after EIReP treatment. The absolute value of complex viscosity and storage modulus increased significantly for the EIReP modified blends, suggesting the improved melt strength and elasticity. The crystallization investigation showed that the cold crystallization peak of PLA phase gradually disappeared after EIReP modification. Instead, the crystallization peak arose during melt cooling process. Consequently, the crystallinity of PLA phase increased from 6.2% to 39.0% as the mNR content increased from 0 to 20 wt%. It was found that the softening temperature of PLA examined by dynamic mechanical analysis increased effectively with the characters of higher modulus compared to the non-modified blends. The EIReP modified blends exhibited excellent mechanical properties with 7-fold increase of impact toughness compared with neat PLA, implying a superior interfacial adhesion and chain interactions between the two polymer phases. Furthermore, the thermogravimetric analysis demonstrated that the thermal stability was slightly enhanced for the EIReP modified blends. Graphical abstract: Image 1 Highlights: Bio-based PLA/mNR blends were prepared by a novel electron induced reactive processing (EIReP) without using any additives. Significantly enhanced melt strength and elasticity was achieved for the EIReP modified blends. The crystallinity of PLA phase increased from 6.2% to 39.0% after EIReP by introducing 20 wt% mNR. The EIReP modified blends exhibited excellent mechanical with 7-fold increase of impact toughness compared with neat PLA.